PENGARUH INTELLECTUAL CAPITAL, LEVERAGE DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN DENGAN KEBIJAKAN DIVIDEN SEBAGAI VARIABEL MODERASI (PERUSAHAAN MANUFAKTUR BEI 2020-2024) - Ghina Mubarok; Ramdani Bayu Putra; Tri Ayu Parwati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to examine the influence of intellectual capital, leverage, and firm size on firm value, with dividend policy as a moderating variable, in manufacturing companies listed on the Indonesia Stock Exchange between 2020 and 2024. The sample selection technique used purposive sampling, selecting 12 companies. The analysis method used moderated regression analysis with Eviews 13.Based on the results of hypothesis testing, it was found that intellectual capital has a significant effect on company value in manufacturing companies listed on the Indonesia Stock Exchange in 2020-2024. Leverage has a significant effect on company value in manufacturing companies listed on the Indonesia Stock Exchange in 2020-2024. Company size does not have a significant effect on company value in manufacturing companies listed on the Indonesia Stock Exchange in 2020-2024. Intellectual capital does not have a significant effect on company value with dividend policy as a moderator in manufacturing companies listed on the Indonesia Stock Exchange in 2020-2024. Dividend policy is able to weaken the influence between intellectual capital on company value. Leverage does not have a significant effect on company value with dividend policy as a moderator in manufacturing companies listed on the Indonesia Stock Exchange in 2020-2024. Dividend policy is able to weaken the influence between leverage on company value. Company size does not have a significant effect on company value with dividend policy as a moderator in manufacturing companies listed on the Indonesia Stock Exchange in 2020-2024. Dividend policy is able to weaken the influence of company size on company value.